Multi-omics-based phenotyping of AFG3L2-mutant lymphoblasts determines key factors of a pathophysiological interplay between mitochondrial vulnerability and neurodegeneration in spastic ataxia type 5 - Oeztuerk, Menekse; Herebian, Diran; Dipali, Kale; Hentschel, Andreas; Rademacher, Nina; Kraft, Florian; Horvath, Rita; Distelmaier, Felix; Meuth, Sven G.; Ruck, Tobias; Schara-Schmidt, Ulrike; Roos, Andreas (Frontiers in Molecular Neuroscience, 2025)
Mitochondrial integrity is fundamental to cellular function, upheld by a network of proteases that regulate proteostasis and mitochondrial dynamics. Among these proteases, AFG3L2 is critical due to its roles in maintaining mitochondrial homeostasis, regulating mitochondrial protein quality, and facilitating mitochondrial biogenesis. Mutations in AFG3L2 are implicated in a spectrum of diseases, including spinocerebellar ataxia type 28 (SCA28) and spastic ataxia 5 (SPAX5), as well as other systemic conditions. This study employs a multi-omics approach to investigate the biochemical impact of AFG3L2 mutations in immortalized lymphoblastoid cell lines derived from a patient with biallelic variants leading to spastic ataxia (SPAX5). Our proteomic analysis revealed AFG3L2 impairment, with significant dysregulation of proteins critical for mitochondrial function, cytoskeletal integrity, and cellular metabolism. Specifically, disruptions were observed in mitochondrial dynamics and calcium homeostasis, alongside downregulation of key proteins like COX11, a copper chaperone for complex IV assembly, and NFU1, an iron-sulfur cluster protein linked to spastic paraparesis and infection-related worsening. Lipidomic analysis highlighted substantial alterations in lipid composition, with significant decreases in sphingomyelins, phosphatidylethanolamine, and phosphatidylcholine, reflecting disruptions in lipid metabolism and membrane integrity. Metabolomic profiling did not reveal any significant findings. Our comprehensive investigation into loss of functional AFG3L2 elucidates a pathophysiology extending beyond mitochondrial proteostasis, implicating a wide array of cellular processes. The findings reveal substantial cellular disturbances at multiple levels, contributing to neurodegeneration through disrupted mitochondrial respiratory chain, calcium homeostasis, cytoskeletal integrity, and altered lipid homeostasis. This study underscores the complexity of SPAX5 pathophysiology and the importance of multi-omics approaches in developing effective strategies to address the impact of loss of functional AFG3L2. Our data also highlight the value of immortalized lymphoblastoid cells as a tool for pre-clinical testing and research, offering a detailed biochemical fingerprint that enhances our understanding of SPAX5 and identifies potential areas for further investigation.